The Ideology of Beauty in Wardah and Sariayu Advertisements - Efraim Goldsteel (Kata Kita: Journal of Language, Literature, and Teaching, 2023)
The aim of the study is to analyze the construction and promotion of the ideology of beauty in advertisements from the brands Wardah and Sariayu. To interpret the data, the researcher employed Fairclough's three-dimensional model, which allows for a comprehensive analysis of discourse. Throughout the analysis, the researcher observed the use of various discursive strategies, such as puffery, pseudo-scientific claims, emotional appeals, and linking techniques. In the case of Wardah advertisements, the emphasis was placed on the importance of meeting beauty standards. The advertisements also associated their products with some religious values to appeal a specific target audience. On the other hand, Sari Ayu advertisements focus on the concept of self-improvement and natural complexion. Rather than conforming to societal beauty standards, the emphasis to promote the idea that individuals can be beautiful and confident without adhering strictly to conventional beauty standard.